2022
DOI: 10.3390/antiox11071300
|View full text |Cite
|
Sign up to set email alerts
|

Increase of HO-1 Expression in Critically Ill COVID-19 Patients Is Associated with Poor Prognosis and Outcome

Abstract: Heme-oxygenase (HO)-1 is a cytoprotective enzyme with strong antioxidant and anti-apoptotic properties and previous reports have also emphasized the antiviral properties of HO-1, either directly or via induction of interferons. To investigate the potential role of HO-1 in patients with coronavirus disease 2019 (COVID-19), the present study assessed changes in HO-1 expression in whole blood and tissue samples. Upregulation of HO-1 protein was observed in lung, liver, and skin tissue independently of severe acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(25 reference statements)
0
7
2
Order By: Relevance
“…One human sepsis study reported that high HO-1 levels were associated with sepsis severity and low survival [ 7 ]. Increased HO-1 expression has been found in severe-to-critically ill patients with COVID-19, with a poor survival prognosis [ 8 ]. However, the role of heme catabolism in COVID-19-related sepsis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One human sepsis study reported that high HO-1 levels were associated with sepsis severity and low survival [ 7 ]. Increased HO-1 expression has been found in severe-to-critically ill patients with COVID-19, with a poor survival prognosis [ 8 ]. However, the role of heme catabolism in COVID-19-related sepsis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated increased HMOX mRNA expression in circulating leukocytes in COVID-19 patients. 39 Other study which measured circulating HO-1 levels in blood from these patients also demonstrated upregulation of HO-1 levels in a population of eight patients. 19 More recently, a larger study encompassing 64 patients demonstrated that HO-1 is consistently associated with clinical and laboratory markers of disease severity, and that its measurement could refine prediction models for ICU admission.…”
Section: Discussionmentioning
confidence: 80%
“…Nrf2 is a transcription factor that binds to the antioxidant response element (ARE) and activates the expression of various antioxidant genes, such as HO-1 and NQO1 [ 47 49 ]. HO-1 is an enzyme that catalyzes the degradation of heme, a pro-oxidant molecule known as biliverdin, carbon monoxide and iron, which have anti-inflammatory, anti-apoptotic and cytoprotective effects [ 50 ]. NQO1 can reduce quinones to hydroquinone, which can be further conjugated with glutathione and excreted from the cells [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%